THE EFFECT OF DISCOVERY LEARNING MODEL IN WRITING PROCEDURE TEXT - uswatun hasanah yuniarsito.s (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract Abstract: The aims of the research to know the extent of the using discovery learning model in teaching students’ writing in procedure text, the extent of the students’ writing in procedure text before and after the using discovery learning model, and to know whether there is any significant effect of between discovery learning model on students’ writing in procedure text to the eleventh grade students of SMA Negeri 1 Sihapas Barumun. The research is conducting by using experimental method (pretest posttest one group design) with 31 students as the sample and they are taking by using cluster sampling technique from 2 classes as population. Test and observation are using in collecting the data. Based on the data analysis, it can be found the average of using discovery leaning model in teaching students’ writing in procedure text is 74.00 categorized “good”, and the mean score of students’ writing in procedure text before and after the using discovery learning model to the eleventh grade students of SMA Negeri 1 Sihapas Barumun is 68.13 categorized “enough” and 77.52 categorized “good”. Furthermore, based on inferential statistic by using ttest, the writer find ttest less than ttable (4.17 > 1.697). It means, there is a significant effect of the using discovery learning model on students’ writing in procedure text to the eleventh grade students of SMA Negeri 1 Sihapas Barumun. Keywords: Discovery Learning Model, Writing Ability, Procedure Text Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana penggunaan model discovery learning, tingkat pemahaman siswa dalam menulis teks prosedur sebelum dan sesudah menggunakan model discovery learning, dan untuk mengetahui apakah ada pengaruh yang signifikan antara menggunakan model discovery learning pada siswa. Kemampuan siswa menulis teks prosedur di kelas sebelas SMA Negeri 1 Sihapas Barumun. Penelitian ini dilakukan dengan menggunakan model eksperimental (pretest postest one group design) dengan 31 siswa sebagai sampel dan diambil dengan menggunakan teknik cluster sampling dari 2 kelas. Tes dan observasi digunakan dalam mengumpulkan data. Berdasarkan analisis data, ditemukan rata-rata menggunakan model discovery learning 74.00 dikategorikan